Chlamydial Heat Shock Proteins and Disease Pathology: New Paradigms for Old Problems? - D. LaVerda; M. V. Kalayoglu; G. I. Byrne (Hindawi Limited, 1999)
The mucosal pathogen Chlamydia trachomatis affects hundreds of millions of people worldwide and is a significant cause of sexually transmitted disease. Although most acute infections can be easily managed, complications often occur that can be especially severe in women. It has been proposed that increased exposure to conserved chlamydial antigens, such as through reinfection or persistent infection, results in chronic inflammation and tissue scarring and contributes to the pathogenesis of endometrial and fallopian tube damage. This immunopathologic damage is believed to be a principal cause of ectopic pregnancy and tubal factor infertility. The chlamydial heat shock protein Hsp60, a homolog of Escherichia coli GroEL, has been identified as one protein capable of eliciting intense mononuclear inflammation. Furthermore, several studies have revealed a correlation between Hsp60 responses and the immunopathologic manifestations of human chlamydial disease. The role of additional antigens in the immunopathologic response to chlamydiae is currently undefined. A prime candidate, however, is the chlamydial GroES homolog Hspl0, which is genetically and physiologically linked to Hsp60. Recent studies provide data to suggest that immune reactivity to Hspl0 is significantly associated with tubal infertility in a chlamydiae-exposed population. Chlamydia pneumoniae is a more recently defined chlamydial species that has been implicated in a variety of ways with chronic disease processes, such as adult onset asthma and atherosclerosis. Evidence indicates that Hsp60 is present in human atheroma and may play a role in lesion development by direct activation of macrophages. Hsp60 causes the elaboration of inflammatory cytokines, the induction of metalloproteinase, and the oxidation of low density lipoprotein. Each of these events is directly associated with the progress of atherosclerosis. Thus, chlamydial heat shock proteins may function in at least two ways to promote chronic disease: first by direct antigenic stimulation and second as signal transducers that result in macrophage activation. These concepts in disease pathology are discussed in the context of chlamydial infections. Infect. Dis. Obstet. Gynecol. 7:64-71, 1999.